Proton Pump Inhibitors Directly Block hERG-Potassium Channel and Independently Increase the Risk of QTc Prolongation in a Large Cohort of US Veterans. (18th June 2021) - Lazzerini, Pietro Enea; Cartocci, Alessandra; Qu, Yongxia Sarah; Saponara, Simona; Furini, Simone; Fusi, Fabio; Fabris, Frank; Gamberucci, Alessandra; El-Sherif, Nabil; Cevenini, Gabriele; Pettini, Francesco; Laghi-Pasini, Franco; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Worldwide, there are millions of chronic proton pump inhibitor (PPI) users, often without a compelling indication. Evidence indicates that PPI treatment can increase mortality, in part, due to a higher risk of heart rate–corrected QT interval-related malignant arrhythmias. Drug-induced hypomagnesemia is currently believed to be the only underlying mechanism, and, therefore, serum magnesium monitoring is recommended to minimize arrhythmic risk. However, recent data suggest that PPIs might also directly interfere with cardiac electrophysiology. To test this hypothesis, a translational study was performed using a combination of electrophysiology, molecular dynamics simulations, and population data. Methods: First, the effect of different PPIs on the human ether-a-go-go-related gene potassium channel (hERG) current was evaluated in human embryonic kidney 293 cells expressing hERG. Then, free-energy calculations were performed to investigate the binding of these drugs to hERG. Finally, the impact of PPIs on the risk of heart rate–corrected QT interval prolongation was assessed in a retrospective observational cohort of 3867 US veterans, including 1289 PPI-treated subjects. Results: Clinically relevant concentrations of different PPIs induced a significant inhibition of the hERG current in vitro, pantoprazole and lansoprazole being the most potent compounds. Atomic simulations demonstrated that such a blocking class effect is likely due to direct PPIs binding to hERG channel pore cavity. Accordingly, in a US veterans cohort, PPI treatment was independently associated with an ≈20% to 40% increased risk of heart rate–corrected QT interval prolongation, also regardless of hypomagnesemia. Moreover, a synergistic interaction between PPIs and most of the traditional QT-prolonging risk factors was demonstrated. Conclusions: Altogether, this study provides, for the first time, strong evidence that PPIs can per se promote heart rate–corrected QT interval prolongation, by directly inhibiting hERG function. A careful evaluation of the benefit/risk ratio is recommended whenever PPIs are administered in subjects with other QT-prolonging risk factors, even in the absence of hypomagnesemia.